A universal method for the preparation of functional ITO electrodes with ultrahigh stability. Issue 31 (19th March 2015) - Zhang, Xiaowei; Lou, Baohua; Li, Dongyue; Hong, Wei; Yu, You; Li, Jing; Wang, Erkang
Abstract : A novel electrodeposition strategy on an ITO surface: a universal method for electrodeposition of various materials onto the ITO substrate with unprecedented mechanical stability. Abstract : A universal method for electrodeposition of various materials onto an indium tin oxide (ITO) coated substrate with high mechanical stability, which solves one of the most important problems concerning the modified ITO electrodes in practical applications, is presented.